ChemInform Abstract: Conformational Control of Cofactors in Nature — The Influence of Protein‐Induced Macrocycle Distortion on the Biological Function of Tetrapyrroles. Issue 3 (29th December 2015) - Senge, Mathias O.; MacGowan, Stuart A.; O'Brien, Jessica M.
Abstract: Review: [284 refs.